Unemployment in Greece : A Survey of the Issues - Demekas, Dimitri (IMF Working Papers; Working Paper ;, 1996)
The Greek unemployment rate rose from 2 percent in the 1960s to 9-10 percent in the 1990s. This reflected the increase in female participation rates, the slowdown in growth, the restructuring of production, and the increased mismatch between jobs and job seekers. But the most crucial factor was the persistence of real wage aspirations. The paper develops and tests a model that attributes this to the rapid expansion in the number of easy, life-time government jobs and the increase in the public/private wage differential during the 1980s.